Prospectively randomised trial of proximal gastric vagotomy either with or without pyloroplasty in treatment of uncomplicated duodenal ulcer. Issue 6091 (1st October 1977) - Wastell, C; Colin, J; Wilson, T; Walker, E; Gleeson, J; Zeegen, R
Abstract : A consecutive series of 100 men with uncomplicated duodenal ulcer was randomly divided into two groups: one group of 52 underwent proximal gastric vagotomy (PGV), the other group (48) underwent PGV with pyloroplasty (PGVP). Preoperative peak acid output (PAOP) was measured in all patients. Those with a higher preoperative PAOP were significantly more likely to develop recurrent ulceration. Three patients developed recurrent ulceration after PGV and seven after PGVP. Dumping was both more common and more severe after PGVP than PGV. An overall satisfactory result was achieved in 92% after PGV and 81% after PGVP. We conclude that combining pyloroplasty with PGV has no appreciable advantages.